Multiple Genes of Symbiotic Plasmid and Chromosome in Type II Peanut Bradyrhizobium Strains Corresponding to the Incompatible Symbiosis With Vigna radiata - Wu, Yue; Li, Yong Hua; Shang, Jiao Ying; Wang, En Tao; Chen, La; Huo, Bin; Sui, Xin Hua; Tian, Chang Fu; Chen, Wen Feng; Chen, Wen Xin (Frontiers in Microbiology, 2020)
Rhizobia are capable of establishing compatible symbiosis with their hosts of origin and plants in the cross-nodulation group that the hosts of origin belonged to. However, different from the normal peanut Bradyrhizobium (Type I strains), the Type II strains showed incompatible symbiosis with Vigna radiata. Here, we employed transposon mutagenesis to identify the genetic loci related to this incompatibility in Type II strain CCBAU 53363. As results, seven Tn5 transposon insertion mutants resulted in an increase of nodule number on V. radiata. By sequencing analysis of the sequence flanking Tn5 insertion, six mutants were located in the chromosome of CCBAU 53363, respectively encoding acyltransferase (L265), hypothetical protein (L615) -unique to CCBAU 53363, two hypothetical proteins (L4 and L82), tripartite tricarboxylate transporter substrate binding protein (L373), and sulfur oxidation c-type cytochrome SoxA (L646); while one mutant was in symbiotic plasmid encoding Alanine dehydrogenase (L147). Significant genetic differences were observed in L147 genes between the Type II strains (in symbiotic plasmid) and Type I strains (in chromosome) and changed the corresponding protein 3D structures. Conversely, strains in both types shared high homologies in the chromosome genes L373 and L646 and in their protein 3D structures. These data indicated that the symbiotic plasmid gene in Type II strains might be directly affected their symbiosis incompatibility through protein structures, whereas the chromosome genes might be indirectly involved in this process by regulating the plasmid symbiosis genes. The seven genes may initially explain the complication associated with symbiotic incompatibility.